Quantifying the Role of Firms in Intergenerational Mobility - Caue Dobbin; Tom Zohar (Center for Economic Studies and ifo Institute (CESifo), 2023)
We investigate the role of firms in intergenerational mobility by decomposing the intergenerational elasticity of earnings (IGE) into firm-IGE and individual-IGE using a two-way fixed effects framework. Using data from Israel, we find that the firm component is responsible for 22% of the overall IGE. We then explore potential mechanisms and find that education differences explain a large share of the individual-IGE, while place of residence and demographics are more important for the firm-IGE. Guided by these empirical patterns, we develop a novel method to estimate the role of skill-based sorting and find that it accounts for approximately half of the firm-IGE. Our results provide evidence that the intergenerational transmission of earnings encompasses more than just human capital, and highlight the importance of promoting equal access to high-paying firms and reducing labor market segregation in efforts to enhance equality of opportunity.
Keywords: J62; J31; J60; 330; intergenerational mobility; firm wage premium; assortative matching; skill-based sorting